The EPPO/OLAF compendium of national procedures: Netherlands - Hauck, Pierre; Schneider, Jan-Martin; Justus Liebig University Giessen (My University, 2025)
This Dutch EPPO/OLAF volume examines the Dutch law governing the activities of the EPPO in the Netherlands and contains references to the EPPO Regulation and the Dutch Adoption Act (Wet van 17 maart 2021). It also explores relevant legal information for OLAF's seconded national experts, its investigators and the investigative tasks of its national partners in external investigations.
Keywords: ddc:340; ddc:320